1979
DOI: 10.3758/bf03208301
|View full text |Cite
|
Sign up to set email alerts
|

The modification of speech perception and production in second-language learning

Abstract: Seventy-two native Spanish speaking children enrolled in programs to teach English as a second language and 24 monolingual English children were tested in speech perception and production tasks with the purpose of determining whether or not there is learning at the phonetic level during second-language acquisition. Performance with the phonetic feature voicing was studied by means of measuring changes in the perception and production of the acoustic property voice onset time. Variables of interest across Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
53
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 19 publications
10
53
2
Order By: Relevance
“…Native English children may identify shortand long-lag stops more reliably than French children because they learn to make use of the F| transition duration and onset frequency differences which co-occur with the VOT difference distinguishing shortand long-lag English stops. Unfortunately, the hypothesis concerning formant transi tion duration cannot be evaluated, for neither Zlatin and Koenigsknecht [see Zlatin, 1974] nor Williams [1979aWilliams [ , 1979b provided information concerning the dura tion of the F| transitions in their synthetic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Native English children may identify shortand long-lag stops more reliably than French children because they learn to make use of the F| transition duration and onset frequency differences which co-occur with the VOT difference distinguishing shortand long-lag English stops. Unfortunately, the hypothesis concerning formant transi tion duration cannot be evaluated, for neither Zlatin and Koenigsknecht [see Zlatin, 1974] nor Williams [1979aWilliams [ , 1979b provided information concerning the dura tion of the F| transitions in their synthetic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, the native segment is produced in a manner more similar to a second-language segment. Williams [1979] found that child native Spanish learners of English produced Spanish voiced stops with less voicing lead and voiceless stops with more voicing lag than did Spanish monolingual adults and that, furthermore, the younger children differed to a greater extent. Flege and Hillenbrand [1984] and Flege [1987] found that highly experienced late learners of English produced their native French stops with VOT values intermediate between their first-and second-languages.…”
Section: Introductionmentioning
confidence: 99%
“…Nonnalives who learn English as an L2 often produce English /p t k/ with shorter VOT values than do English monolinguals [c.g.. Carmazza el al" 1973: Williams, 1979b: Flege and Hillenbrand, 1984Flege and Ecfting. 1988: Major.…”
Section: Introductionmentioning
confidence: 99%